Analysis of uric acid and blood glucose levels on the lifestyle of the population in Lebosari village, Kangkung district - Hani Nur Endah; Rosa Ezizya Febriani; Iffah Syafaatul Arabia (Community Research and Application Journal (CRAJ), 2024)
Cardiovascular disease (CVD) is a significant global health problem, including in Indonesia. Modifiable CVD risk factors, such as unhealthy lifestyles, play an essential role in the development of this disease. This study aims to analyze the relationship between lifestyle and uric acid and blood glucose levels in the Lebosari Village community, Kangkung district, to understand CVD risk factors at the Lebosari Village level. This study adopted a descriptive observational approach to comprehensively describe the profile of uric acid levels in the population studied. Through direct observation of the examination results, this study aims to accurately show the prevalence and distribution of uric acid levels in the field. From the activities that have been carried out, the results of uric acid examinations in the Lebosari village community, Kangkung district, showed that out of 50 samples, there was 1 male with normal uric acid levels in women, 39 normal, 4 had gout, and 4 had high blood sugar levels.